Influence of Piper nigurm. L on Corrosion Inhibition of Mild Steel in Citric Acid Medium - Matheswaran, P.; Ramasamy, A.K. (Asian Journal of Chemistry, 2011)
The inhibition efficiency of an aqueous extract of Piper nigurm. L in controlling corrosion of mild steel at pH 12 has been evaluated by weight loss method in the absence and presence of inhibitor in citric acid medium at different concentration. The result showed that the corrosion inhibition efficiency of these compounds was found to vary with the different time interval at room temperature. It was also found that the corrosion inhibition behaviour of Piper nigurm. L is greater in 2N citric acid than 1N citric acid medium. So Piper nigurm. L can be used as a good inhibitor for preventing mild steel material. The surface analysis study confirms the corrosion of the mild steel and its inhibition effect by the inhibitor Piper nigrum L.